Surgical patient satisfaction toward perioperative nursing care provided in Hospital Universiti Sains Malaysia (Hospital USM) - Jun, Chua Kok (Universiti Sains Malaysia, 2015)
Human satisfaction is a very complex concept, involving many components such as physical, emotional, mental, social, and cultural factors. Multiple definitions of this concept and theories of satisfaction have emerged mainly from the field of behavioral sciences and consumerism. Previous study found that patient satisfaction with perioperative care remains largely undiscovered, with only little investigations available. Thus, the purpose of this study is to determine the level of surgical patients’ satisfaction toward perioperative nursing care provided in Hospital USM. The number of population in this study was 60 surgical patients that were admitted for perioperative care in the surgical wards at Hospital USM. The research design was a cross-sectional and quantitative study. The sampling method used is a non-probability method via convenient sampling method by using Leiden Perioperative care Patient Satisfaction questionnaire (LPPSq). The result showed that the level of satisfaction among surgical patients is completely satisfied (M=69.33, SD=9.436). There is no significant association between demographic data, health related data and patient satisfaction score. Overall, patients who are male, single, higher education level, Malays and Chinese, and those who undergoing major surgery are more satisfied with perioperative nursing care provided. This study reflects that the level of satisfaction among surgical patients toward perioperative nursing care provided in Hospital USM is completely satisfying.